Host-specific sensing of coronaviruses and picornaviruses by the CARD8 inflammasome. - Brian V Tsu; Rimjhim Agarwal; Nandan S Gokhale; Jessie Kulsuptrakul; Andrew P Ryan; Elizabeth J Fay; Lennice K Castro; Christopher Beierschmitt; Christina Yap; Elizabeth A Turcotte; Sofia E Delgado-Rodriguez; Russell E Vance; et al. (PLoS Biology)
Hosts have evolved diverse strategies to respond to microbial infections, including the detection of pathogen-encoded proteases by inflammasome-forming sensors such as NLRP1 and CARD8. Here, we find that the 3CL protease (3CLpro) encoded by diverse coronaviruses, including Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), cleaves a rapidly evolving region of human CARD8 and activates a robust inflammasome response. CARD8 is required for cell death and the release of pro-inflammatory cytokines during SARS-CoV-2 infection. We further find that natural variation alters CARD8 sensing of 3CLpro, including 3CLpro-mediated antagonism rather than activation of megabat CARD8. Likewise, we find that a single nucleotide polymorphism (SNP) in humans reduces CARD8's ability to sense coronavirus 3CLpros and, instead, enables sensing of 3C proteases (3Cpro) from select picornaviruses. Our findings demonstrate that CARD8 is a broad sensor of viral protease activities and suggests that CARD8 diversity contributes to inter- and intraspecies variation in inflammasome-mediated viral sensing and immunopathology.